Long memory in Turkish Unemployment Rates - Luis A. Gil-Alana; Zeynel Abidin Ozdemir; Aysit Tansel (Global Labor Organization (GLO), 2017)
In this paper we have examined the unemployment rate series in Turkey by using long memory models and in particular employing fractionally integrated techniques. Our results suggest that unemployment in Turkey is highly persistent, with orders of integration equal to or higher than 1 in most cases. This implies lack of mean reversion and permanence of the shocks. We found evidence in favor of mean reversion in the case of female unemployment and this happens for all the groups of non-agricultural, rural, urban and youth unemployment series. The possibility of non-linearities are observed only in the case of female unemployment and the degree of persistence is higher in the cases of female and youth unemployment series. Important policy implications emerge from our empirical results. Labor and macroeconomic policies will most likely have long lasting effects on the unemployment rates.
Keywords: C22; E24; 330; Unemployment; hysteresis; NAIRU; fractional integration; Turkey